2015
DOI: 10.1155/2015/704121
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Correlates of Compensatory Adjustments to the Glottic and Supraglottic Structures in Patients with Unilateral Vocal Fold Paralysis

Abstract: The goal of this study was to analyse perceptually and acoustically the voices of patients with Unilateral Vocal Fold Paralysis (UVFP) and compare them to the voices of normal subjects. These voices were analysed perceptually with the GRBAS scale and acoustically using the following parameters: mean fundamental frequency (F0), standard-deviation of F0, jitter (ppq5), shimmer (apq11), mean harmonics-to-noise ratio (HNR), mean first (F1) and second (F2) formants frequency, and standard-deviation of F1 and F2 fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…The main results of this research corroborate with studies that highlight the source-filter coupling and the change in the range of motion and posture of the articulators due to alteration in the glottal source (4,7,9,21,22) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The main results of this research corroborate with studies that highlight the source-filter coupling and the change in the range of motion and posture of the articulators due to alteration in the glottal source (4,7,9,21,22) .…”
Section: Discussionsupporting
confidence: 88%
“…In turn, individuals with voice disorder may adjust articulator positioning and movement, either as a compensatory mechanism or as a co-occurrence of this disorder. Such adjustments, associated with the irregularity and noise present in dysphonic voices, may influence the production of vowel (3,4) or consonant phonemes (5,6) , decrease speech intelligibility, and compromise verbal message transmission (3,4,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Strong correlation has been shown to exist between vocal tract morphology and vocal characteristics in both dysphonic 1 and nondysphonic subjects. 1,2 Jesus et al 3 reported higher values for the second formant (second preferred harmonic) in patients with unilateral vocal fold paralysis, in comparison to controls. Similarly, Titze 2 described clustering of the first two formants in patients with unilateral vocal fold paralysis, alluding to the narrowing of the vocal tract in compensation for inefficient phonation.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic voice analysis [20,21] is an effective and noninvasive tool that can be used to confirm an initial diagnosis and provide an objective determination of the impairment [38]. It is also an important tool to an early detection and treatment of laryngeal tumors that can reduce both morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various scientific studies along the past 40 years that compare, acoustically, normal and disordered voices [8,10,16,27,31,37]. For Portuguese, there have been some voice research on vocal quality [3,6,33,34,41,42,49], distinction between pathological voice and normal voice through acoustic analysis [5,12,13,21,36] and the prevalence of laryngeal disorders [7,39]. However, there are no known open access databases that allow the comparison of voice studies.…”
Section: Introductionmentioning
confidence: 99%